Pengaruh Display Terhadap Perilaku Impulse Buying Di Transmart Bahu-Manado - Tawas, Indry F. N.; Tamengkel, Lucky F.; Punuindoong, Aneke Y. (Sam Ratulangi University, 2019)
This study aims to determine; the effect of variable display on impulse buying on Transmart Bahu-Manado.; to determine how much influence the display has on the behavior of impulse buying on Transmart Bahu-Manado. Consumer behavior is an action that is directly involved in acquiring, consuming, and spending, a product or service, including the process of decision that precedes and follows this action. Impulse buying is a purchase that is not planned in advance or is a spontaneous purchase, impulse buying occurs when consumers suddenly experience a strong and strong desire to buy something as soon as possible, spontaneously, reflex, sudden and automatic. Data obtained from questionnaires. The samples in this study were 97 respondents taken from the Accidental Sampling method. The analysis technique used simple regression technique and coefficient of determination (R square). The results of the study show that: display variables have a significant effect on impulse buying. It is expected that Transmart Bahu-Manado can maintain and even improve the arrangement of its products.